LOCATION PATTERNS OF HOUSEHOLD TEMPE INDUSTRY IN RASAU JAYA DISTRICT, KUBU RAYA DISTRICT - Junaidi, Junaidi; Buwono, Sri; Anasi, Putri Tipa (GEOREFERENCE, 2024)
A study on household soy tempeh industry in Rasau Jaya Subdistrict, Kubu Raya Regency aims to determine the distribution pattern of soy tempeh household industry locations. This research utilizes the Nearest Neighbor Analysis method and a quantitative descriptive approach with data collection through observation, interviews, and documentation. The research findings indicate that the nearest neighbor analysis with a calculated t-value of 0.600 concludes that soy tempeh household industries tend to cluster in certain areas of Rasau Jaya Subdistrict. Factors such as settlement location and geographical aspects, especially the ease of access to raw materials and marketing, influence this distribution pattern. Industrial locations are chosen based on the ease of access to primary raw materials, namely soybeans, obtained from Rasau Raya Traditional Market and Flamboyan Market. Labor employed in this industry operates on a piece-rate system, where workers are compensated based on the completed tasks. The majority of soy tempeh product marketing targets local markets within the village, indicating a focus on the local market in the area. Only a small proportion expands beyond the village but remains within the same district. Thus, the household soy tempeh industry in Rasau Jaya Subdistrict is supported by a clustered distribution pattern influenced by geographical factors, accessibility to raw materials, and a marketing strategy focused on the local market.